Pine-based hard carbon material, sodium-ion battery negative electrode, sodium-ion battery and preparation method and application of sodium-ion battery

By carbonizing, pickling and segmented high temperature treatment of pine wood, preparing the pine -based hard carbon material for the negative electrode of sodium ion battery, solve the problem of poor capacity and magnification of the existing biomass hard carbon materials, realize The high ratio of sodium ion batteries, good magnification performance and cycle stability.

CN119349548AActive Publication Date: 2025-01-24GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202411494334.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing biomass hard carbon materials used in sodium ion batteries have problems with poor specific capacity and rate performance.

Method used

By carbonizing, pickling, and segmented high-temperature treatment of pine wood, pine wood-based hard carbon materials were prepared and used as negative electrodes for sodium-ion batteries. The treatment process includes staged high-temperature treatments between 500-600°C and 1300-1600°C to form a highly crystalline material and improve its pore structure.

Benefits of technology

This method makes sodium ion batteries have high ratio and good multipliers, and at the same time improve the cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349548A_ABST
    Figure CN119349548A_ABST
Patent Text Reader

Abstract

The invention relates to a pine-based hard carbon material as well as a preparation method and application thereof. The preparation method of the pine-based hard carbon material comprises the following steps: carrying out carbonization treatment on pine, then carrying out acid pickling, and finally carrying out segmented high-temperature treatment to obtain the pine-based hard carbon material. The pine-based hard carbon material is used for preparing the negative electrode of the sodium-ion battery, so that the sodium-ion battery has high specific capacity and good rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and more specifically, to a pine wood-based hard carbon material, a sodium ion battery negative electrode, a sodium ion battery, and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are an emerging battery technology. Compared with traditional lithium-ion batteries, sodium is a relatively cheap and abundant element. It is easier to obtain and produce than lithium, which is expected to reduce the cost of batteries. Sodium is more abundant on Earth, which means a sustainable energy supply chain. Sodium-ion batteries also have a higher energy density, which means they can store more energy. However, there are still some technical problems that have not been solved for sodium-ion batteries: the charge and discharge rate of sodium-ion batteries is slow, which limits their rapid charge and discharge; sodium-ion batteries have poor charge and discharge cycle performance, resulting in a short service life.

[0003] In order to overcome these difficulties, researchers have developed hard carbon materials. Hard carbon materials have high conductivity, which is beneficial to the rapid transfer of charge during the charging and discharging process of sodium ion batteries, and improves the rapid charging and discharging performance of sodium ion batteries. Compared with soft carbon materials, hard carbon materials can improve the cycle performance of batteries and extend the service life of batteries. Among them, biomass hard carbon materials are environmentally friendly, do not contain harmful substances, and are beneficial to reducing the impact on the environment; they are inexpensive and easy to obtain, which effectively reduces the manufacturing cost of sodium ion batteries and is more competitive in commercial applications. There are many existing research reports on biomass hard carbon, such as a Chinese patent entitled A Two-Stage Carbonization Preparation Method for Biomass Hard Carbon Materials.

[0004] However, biomass hard carbon materials still have shortcomings. Due to their unstable structure, the rate performance of sodium ion batteries is poor. In addition, the specific capacity of sodium ion batteries is poor, which limits their application in fields with large capacity requirements. Therefore, it is necessary to develop a biomass hard carbon material that enables sodium ion batteries to have good specific capacity and rate performance. Summary of the invention

[0005] The primary purpose of the present invention is to overcome the problems of poor specific capacity and rate performance of the above-mentioned existing biomass hard carbon materials for sodium ion batteries, and to provide a method for preparing pine wood-based hard carbon materials. The preparation method carbonizes, pickles and performs segmented high-temperature treatment on pine wood, and the obtained pine wood-based hard carbon materials are used to prepare the negative electrode of the sodium ion battery, which can make the sodium ion battery have high specific capacity and good rate performance; in addition, it can also make the sodium ion battery have good cycle stability.

[0006] A further object of the present invention is to provide a pine wood-based hard carbon material.

[0007] A further object of the present invention is to provide an application of the above-mentioned pine wood-based hard carbon material in the preparation of a negative electrode for a sodium ion battery.

[0008] A further object of the present invention is to provide a negative electrode for a sodium ion battery.

[0009] A further object of the present invention is to provide a sodium ion battery.

[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0011] A method for preparing a pine wood-based hard carbon material comprises the following steps:

[0012] The pine wood is carbonized, pickled, and finally subjected to staged high-temperature treatment to obtain the pine wood-based hard carbon material;

[0013] The process of the segmented high temperature treatment is: first keep at 500-600°C for 1-2 hours, then keep at 1300-1600°C for 1-4 hours, and finally keep at 500-600°C for 1-2 hours.

[0014] Pine is a widely distributed plant with abundant and renewable resources. Hard carbon prepared from pine has good cycle performance, so hard carbon prepared from pine helps to reduce the overall production cost of sodium-ion batteries. However, hard carbon prepared from pine has weak sodium storage capacity and slow charge transfer rate, which leads to poor specific capacity and rate performance of sodium-ion batteries.

[0015] The inventors of the present invention have found that by first carbonizing the pine wood, then pickling it, and finally subjecting it to a staged high-temperature treatment, the obtained pine wood-based hard carbon material can be used to prepare the negative electrode of a sodium ion battery, which can enable the sodium ion battery to have a high specific capacity and good rate performance.

[0016] Among them, the staged high temperature treatment includes three stages of treatment at different temperatures in sequence, and its mechanism is:

[0017] Maintaining the temperature at 500-600°C (first stage temperature) for a period of time helps the material to undergo a structural stabilization treatment at a relatively low temperature, thereby reducing the structural changes or defects that may occur in the material during subsequent higher temperature treatment (second stage temperature), thereby facilitating the formation of a pore structure during the higher temperature treatment (second stage temperature).

[0018] In the 1300-1600℃ stage (the second temperature stage), the material is transformed into a highly crystallized state. The higher the crystallinity of the material, the better its conductivity and cycle stability. More importantly, under this high temperature condition, more pore structures are formed inside the material. The pore structures can provide more storage space for sodium ions, thereby increasing the energy density and charge transfer rate of the battery, thereby improving the specific capacity and rate performance of the sodium-ion battery.

[0019] After high temperature treatment, certain stress will accumulate inside the material, and rapid cooling may lead to a decrease in the performance of the material (such as reduced hardness, increased brittleness, etc.). After the second stage temperature, the present invention is maintained at 500-600°C (third stage temperature) for 1-2 hours, so that the stress accumulated after high temperature treatment can be gradually released, reducing the risk of cracking or deformation of the material due to rapid cooling, which is conducive to improving the capacity and rate performance of the sodium ion battery.

[0020] If the staged high-temperature treatment does not include the first temperature stage, it is not conducive to the formation of the pore structure in the pine wood-based hard carbon material; if the staged high-temperature treatment does not include the third temperature stage, the pore structure formed in the pine wood-based hard carbon material will change (crack or close) during the cooling process. Both situations are not conducive to improving the capacity and rate performance of sodium ion batteries.

[0021] In addition, the present invention also requires acid washing during the segmented high-temperature treatment, which can remove metal components in the carbon material, and is also conducive to the formation of a pore structure.

[0022] That is, the present invention performs carbonization treatment, acid washing and segmented high-temperature treatment on pine wood, and the obtained pine wood-based hard carbon material is used to prepare the negative electrode of the sodium ion battery, which can make the sodium ion battery have high specific capacity and good rate performance; in addition, it can also make the sodium ion battery have good cycle stability.

[0023] Preferably, before the carbonization treatment, the method further comprises the step of mixing the pine wood and a pore-forming agent.

[0024] More preferably, the pine wood and the pore-forming agent are mixed by ball milling.

[0025] More preferably, the ball milling speed is 400-600 rad / min, and the time is 8-12 h.

[0026] More preferably, the pore-forming agent is at least one of phosphoric acid, citric acid or potassium hydroxide.

[0027] More preferably, the mass ratio of the pine wood to the pore-forming agent is 1:(0.1-0.5).

[0028] More preferably, the mass ratio of the pine wood to the pore-forming agent is 1:(0.2-0.3).

[0029] More preferably, before the pine wood and the pore-forming agent are mixed, the method further includes a step of drying the pine wood.

[0030] More preferably, the drying temperature is 50-120° C. and the drying time is 16-28 hours.

[0031] Preferably, the carbonization treatment is carried out at a temperature of 400 to 800° C. and for a time of 1 to 5 hours.

[0032] More preferably, the carbonization treatment is carried out at a temperature of 500-600° C. and for a time of 2-3 hours.

[0033] Preferably, the carbonization treatment is performed in an inert gas atmosphere.

[0034] More preferably, the inert gas atmosphere is at least one of a nitrogen atmosphere or an argon atmosphere.

[0035] Preferably, after the carbonization treatment and before the pickling, a grinding step is also included.

[0036] More preferably, the grinding time is 15 to 30 minutes.

[0037] More preferably, the grinding time is 20 to 25 minutes.

[0038] Preferably, the acid washing process is: immersing the obtained carbon material after carbonization treatment in a strong acid solution, stirring at 50-80° C. for 20-30 hours, filtering and washing with deionized water until neutral.

[0039] More preferably, the strong acid solution is at least one of hydrochloric acid, sulfuric acid or nitric acid; and the concentration of the strong acid solution is 0.1 to 3 mol / L.

[0040] Preferably, after the pickling and before the staged high-temperature treatment, a drying step is also included.

[0041] More preferably, the drying temperature is 80-150° C. and the drying time is 30-60 hours.

[0042] Preferably, the process of the staged high temperature treatment is: first increase the temperature to 500-600°C at a rate of 1-5°C / min and keep it for 1-2h, then increase the temperature to 1300-1600°C at a rate of 1-5°C / min and keep it for 1-4h, and finally decrease the temperature to 500-600°C at a rate of 1-5°C / min and keep it for 1-2h.

[0043] Preferably, the process of the staged high temperature treatment is: first keep at 500-600°C for 1-2 hours, then keep at 1500-1600°C for 1-4 hours, and finally keep at 500-600°C for 1-2 hours.

[0044] Regulating the temperature of the second stage at 1500-1600°C is not only beneficial to improving the capacity and rate performance of the sodium ion battery, but also can improve the cycle performance of the sodium ion battery.

[0045] Preferably, the staged high temperature treatment is carried out in an inert gas atmosphere.

[0046] More preferably, the inert gas atmosphere is at least one of a nitrogen atmosphere or an argon atmosphere.

[0047] Preferably, after the segmented high temperature treatment, a grinding step is also included.

[0048] More preferably, the grinding method is ball milling, the rotation speed of the ball mill is 600-800 rad / min, and the time is 8-13 hours.

[0049] A pine wood-based hard carbon material is prepared by any of the above preparation methods.

[0050] The application of the above-mentioned pine wood-based hard carbon material in the preparation of the negative electrode of a sodium ion battery is also within the protection scope of the present invention.

[0051] A sodium ion battery negative electrode is prepared by the following steps: mixing a conductive agent, a binder, a solvent and a pine wood-based hard carbon material to obtain a slurry, coating the obtained slurry on a current collector, and drying to obtain the sodium ion battery negative electrode.

[0052] Preferably, the mass ratio of the conductive agent, the binder and the pine wood-based hard carbon material is (1-4):(1-8):94.

[0053] Preferably, the conductive agent is at least one of graphite black, carbon nanotubes or graphene.

[0054] Preferably, the binder is at least one of polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol or carboxymethyl cellulose.

[0055] Preferably, the solvent is water.

[0056] Preferably, the current collector is at least one of copper foil, aluminum foil or silver foil.

[0057] Preferably, the drying temperature is 40-80° C. and the drying time is 20-48 hours.

[0058] A sodium ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode is the negative electrode of the sodium ion battery described above.

[0059] Preferably, the positive electrode is at least one of a sodium electrode and a sodium vanadium phosphate electrode.

[0060] Preferably, the material of the diaphragm is at least one of glass fiber, polyethylene or polyimide.

[0061] Preferably, the solvent of the electrolyte is at least one of ethylene glycol dimethyl ether, dimethyl carbonate or ethylene carbonate.

[0062] Preferably, the electrolyte of the electrolyte solution is at least one of sodium trifluoromethanecarbonate, sodium hexafluorophosphate or sodium perchlorate.

[0063] Preferably, the concentration of the electrolyte in the electrolyte solution is 0.5 to 1 mol / L.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] The present invention performs carbonization treatment, acid washing and segmented high-temperature treatment on pine wood, and the obtained pine wood-based hard carbon material is used to prepare the negative electrode of the sodium ion battery, which can make the sodium ion battery have high specific capacity and good rate performance; in addition, it can also make the sodium ion battery have good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 This is the XRD pattern of the pine wood-based hard carbon material prepared in Example 1 of the present invention.

[0067] Figure 2 This is a SEM electron microscope scanning image of the pine wood-based hard carbon material prepared in Example 1 of the present invention.

[0068] Figure 3 The button battery made of the pine wood-based hard carbon material prepared in Example 5 of the present invention is -1 Charge and discharge cycle performance diagram under current density.

[0069] Figure 4 The button battery made of pine wood-based hard carbon material prepared in Comparative Example 1 of the present invention is -1 Charge and discharge cycle performance diagram under current density.

[0070] Figure 5 The button battery made of the pine wood-based hard carbon material prepared in Example 5 of the present invention is 300mAg -1 Charge and discharge cycle performance diagram under current density.

[0071] Figure 6 The button battery made of the pine wood-based hard carbon material prepared in Example 6 of the present invention is 300mAg -1 Charge and discharge cycle performance diagram under current density.

[0072] Figure 7 The button battery made of the pine wood-based hard carbon material prepared in Example 7 of the present invention is 300mAg-1 Charge and discharge cycle performance diagram under current density.

[0073] Figure 8 The button battery made of pine wood-based hard carbon material prepared in Comparative Example 1 of the present invention is 300mAg -1 Charge and discharge cycle performance diagram under current density.

[0074] Fig. 9 The button battery made of pine wood-based hard carbon material prepared in Example 5 of the present invention is 20-1500mAg -1 Charge and discharge rate performance diagram under current density;

[0075] Fig.10 The button battery made of pine wood-based hard carbon material prepared in Comparative Example 1 of the present invention is 20-1500mAg -1 Charge and discharge rate performance diagram under current density; DETAILED DESCRIPTION

[0076] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0077] Example 1

[0078] This embodiment provides a method for preparing a pine wood-based hard carbon material, comprising the following steps:

[0079] 1) Dry the pine wood at 80°C for 24 hours, then weigh 20g of it and put it into a ball mill, then add 5g of phosphoric acid solution (concentration is 5mol / L), and ball mill it at a speed of 600rad / min for 10 hours (during the ball milling, stop for 30 minutes after every 30 minutes) to obtain a mixture; then place the mixture in a nitrogen atmosphere, increase the temperature from 25°C to 600°C at a rate of 2°C / min for 3 hours, and obtain a black substance;

[0080] 2) immersing the black substance obtained in step 1) in a 1 mol / L hydrochloric acid solution, stirring at 60° C. for 24 h, filtering and washing with deionized water until neutral, and drying at 80° C. for 48 h to obtain a black powder;

[0081] 3) The black powder obtained in step 2) is placed in a nitrogen atmosphere, and the temperature is increased from 25°C to 600°C at a rate of 2°C / min and maintained for 1 h, then increased to 1500°C (referred to as temperature T) at a rate of 2°C / min and maintained for 2 h, and finally decreased to 600°C at a rate of 2°C / min and maintained for 1 h, and naturally cooled to room temperature. The obtained material is placed in a ball mill and ball milled at a speed of 800 rad / min for 12 h (during the ball milling process, stop for 30 min after every 30 min) to obtain a pine wood-based hard carbon material.

[0082] Example 2

[0083] This embodiment provides a method for preparing a pine wood-based hard carbon material, which is basically the same as that of Embodiment 1, except that the temperature T in step 3) is 1300°C.

[0084] Example 3

[0085] This embodiment provides a method for preparing a pine wood-based hard carbon material, which is basically the same as that of Embodiment 1, except that the temperature T in step 3) is 1600°C.

[0086] Example 4

[0087] This embodiment provides a method for preparing a pine wood-based hard carbon material, which is basically the same as that of Embodiment 1, except that, in step 1), the temperature is raised from 25°C to 500°C at a rate of 2°C / min and maintained for 3h;

[0088] In step 3), the temperature is increased from 25°C to 500°C at a rate of 2°C / min and maintained for 2 h, then increased to 1500°C at a rate of 2°C / min and maintained for 4 h, and finally decreased to 500°C at a rate of 2°C / min and maintained for 2 h.

[0089] Example 5

[0090] This embodiment provides a sodium ion battery negative electrode and a sodium ion battery prepared therefrom, and the preparation process thereof is as follows:

[0091] 1) Polyvinylidene fluoride, graphite black, styrene-butadiene rubber and the pine-based hard carbon material of Example 1 were put into water in a mass ratio of 4:2:2:95, stirred and mixed to obtain a slurry, and the obtained slurry was coated on a copper foil and vacuum dried at 60° C. for 24 h to obtain a negative electrode for a sodium ion battery.

[0092] 2) Assembling the battery in a glove box filled with argon, wherein the negative electrode is the negative electrode of the sodium ion battery obtained in step 1), the positive electrode is a sodium sheet, the diaphragm is glass fiber, and the electrolyte is a 1 mol / L NaCFSO3 ethylene glycol dimethyl ether solution to obtain a sodium ion battery.

[0093] Example 6

[0094] This embodiment provides a sodium ion battery negative electrode and a sodium ion battery prepared therefrom, which are basically the same as Example 5, except that the pine wood-based hard carbon material in step 1) is the pine wood-based hard carbon material in Example 2.

[0095] Example 7

[0096] This embodiment provides a sodium ion battery negative electrode and a sodium ion battery prepared therefrom, which are basically the same as Example 5, except that the pine wood-based hard carbon material in step 1) is the pine wood-based hard carbon material in Example 3.

[0097] Example 8

[0098] This embodiment provides a sodium ion battery negative electrode and a sodium ion battery prepared therefrom, which are basically the same as Example 5, except that the pine wood-based hard carbon material in step 1) is the pine wood-based hard carbon material in Example 4.

[0099] Comparative Example 1

[0100] This comparative example provides a comparative pine wood-based hard carbon material and a sodium ion battery, comprising the following steps:

[0101] 1) First, process according to step 1) and step 2) of Example 1 to obtain a black powder; then place the black powder in a nitrogen atmosphere, increase the temperature from 25°C to 1500°C at a rate of 2°C / min and maintain for 2 hours, and naturally cool to room temperature. The obtained material is placed in a ball mill and ball milled at a speed of 800 rad / min for 12 hours (during the ball milling process, stop for 30 minutes after every 30 minutes) to obtain a comparative pine wood-based hard carbon material.

[0102] 2) The difference from Example 5 is that the pine wood-based hard carbon material of Example 5 is replaced by the comparison pine wood-based hard carbon material of step 1) of this comparative example to obtain a sodium ion battery.

[0103] Performance Testing

[0104] 1. XRD test and morphology characterization

[0105] The pine wood-based hard carbon material of Example 1 was subjected to X-ray diffraction test and scanning electron microscope test respectively. The test results are as follows: Figure 1 and Figure 2 shown. Figure 1 is the XRD spectrum of Example 1, from Figure 1 It can be observed that there are two obvious broad peaks near 23.5° and 43°, which are attributed to the (002) and (100) peaks of amorphous carbon materials. The formation of amorphous carbon materials is the basis for the pine wood-based hard carbon materials prepared by the present invention to have good sodium storage performance and cycle stability. Figure 2 is the scanning electron microscope image of Example 1, from Figure 2The pine wood-based hard carbon material has many pore structures on its surface, which can effectively improve the sodium storage capacity of the pine wood-based hard carbon material. The XRD test and morphology characterization results of the pine wood-based hard carbon materials of Examples 2 to 4 are similar to those of Example 1.

[0106] 2. Electrochemical performance

[0107] The sodium ion batteries of Examples 5 to 7 and the comparative sodium ion battery of Comparative Example 1 were respectively subjected to rate performance tests and cycle stability tests. The test results are as follows: Figures 3 to 7 shown.

[0108] Figure 3 and Figure 4 The sodium ion battery of Example 5 and the comparative sodium ion battery of Comparative Example 1 are respectively -1 The charge and discharge cycle performance diagram under current density. Figure 3 It can be seen that the initial specific capacity of Example 5 is 354 mAhg -1 After 50 cycles, the capacity is 350 mAh g -1 , the capacity retention rate is 98%. Figure 4 It can be seen that the initial specific capacity of comparative example 1 is 298 mAhg -1 After 50 cycles, the capacity is 290 mAh g -1 Its capacity retention rate is 97%. In addition, at 20mAg -1 At the current density, the first coulombic efficiency of Example 5 is 93%, while that of Comparative Example 1 is only 82%.

[0109] Figures 5 to 8 The sodium ion batteries of Examples 5 to 7 and the comparative sodium ion battery of Comparative Example 1 are respectively -1 The charge and discharge cycle performance diagram under current density. Figure 5 It can be seen that the initial specific capacity of Example 5 is 286.8 mAhg -1 After 300 cycles, the capacity is still 280 mAhg -1 , and its capacity retention rate is 98%. Figure 6 It can be seen that the initial specific capacity of Example 6 is 310.5 mAhg -1 After 300 cycles, the capacity is still 240 mAhg -1 The capacity retention rate is 77%, and the battery tends to be stable after 60 cycles, with the specific capacity maintained at 240 mAh g -1 From Figure 7 It can be seen that the initial specific capacity of Example 7 is 286.7 mAhg -1 After 300 cycles, the capacity is still 244 mAhg -1The capacity retention rate is 85%, and the battery tends to be stable after 20 cycles, with the specific capacity maintained at 244 mAh g -1 From Figure 8 It can be seen that the initial specific capacity of comparative example 1 is 281 mAhg -1 After 300 cycles, the capacity decayed to 218 mAh g -1 , and its capacity retention rate is 77%. This shows that the pine-based hard carbon material obtained by the segmented high-temperature treatment of the present invention is used to prepare the negative electrode of the sodium ion battery, which can make the sodium ion battery have a (initial) high specific capacity, and due to the high initial specific capacity, the sodium ion battery still maintains a high specific capacity after multiple cycles.

[0110] Compare Figure 3 and Figure 4 , Figure 5 and Figure 8 It can be seen that the specific capacity and cycle retention rate of Example 5 remain excellent at different current densities, while the cycle stability of Comparative Example 1 at high current density is not as good as that of Example 5.

[0111] Fig. 9 and Fig.10 The sodium ion battery of Example 5 and the comparative sodium ion battery of Comparative Example 1 are respectively 20-1500 mAg -1 The charge and discharge rate performance diagram under current density. Fig. 9 It can be seen that the sodium ion battery of Example 5 has a high conductivity at 20, 30, 60, 120, 240, 300, 600, 900, 1500 and 20 mAg -1 The reversible capacities at different current densities (10 cycles at different current densities) are 315.4, 298.5, 292.3, 280.5, 261.6, 252.6, 229.2, 206.5, 166.2 and 301.4 mAh g -1 .from Fig.10 It can be seen that the comparative sodium ion battery of Comparative Example 1 has a high conductivity at 20, 30, 60, 120, 240, 300, 600, 900, 1500 and 20 mAg -1 The reversible capacities at different current densities (10 cycles at different current densities) are 312.5, 284.2, 275.2, 233.3, 169.7, 149.6, 85.3, 61.4, 42.2 and 290.1 ​​mAh g -1 From the comparison of the data in the two figures, it can be seen that the specific capacity of Example 5 is higher than that of Comparative Example 1 at different current densities, and the specific capacity fluctuation amplitude of Comparative Example 1 under the rate performance test is smaller than that of the comparative example, indicating that the hard carbon material of Example 1 is more stable.

[0112] By comparing the experimental data of Example 5 and Comparative Example 1, it can be seen that the specific capacity, cycle stability and rate performance of Example 5 are better than those of Comparative Example 1. This shows that the pine wood-based hard carbon material after the segmented high-temperature treatment of the present invention is used to prepare a sodium ion battery, and its specific capacity, cycle stability (especially the cycle stability under high current density) and charge and discharge capacity are all improved.

[0113] The performance of the sodium ion battery of Example 8 is similar to that of Example 5.

[0114] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a pine wood-based hard carbon material, characterized in that: The steps include: The pine wood is carbonized, pickled, and finally subjected to staged high-temperature treatment to obtain the pine wood-based hard carbon material; The process of the segmented high temperature treatment is: first keep at 500-600°C for 1-2 hours, then keep at 1300-1600°C for 1-4 hours, and finally keep at 500-600°C for 1-2 hours.

2. The preparation method according to claim 1, characterized in that: Before the carbonization treatment, the method further comprises the step of mixing the pine wood and a pore-forming agent.

3. The preparation method according to claim 2, characterized in that: The pore-forming agent is at least one of phosphoric acid, citric acid or potassium hydroxide.

4. The preparation method according to claim 1, characterized in that: The temperature of the carbonization treatment is 400-800° C. and the time is 1-5 hours.

5. The preparation method according to claim 1, characterized in that: The process of the segmented high temperature treatment is: first keep at 500-600°C for 1-2 hours, then keep at 1500-1600°C for 1-4 hours, and finally keep at 500-600°C for 1-2 hours.

6. A pine wood-based hard carbon material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the pine wood-based hard carbon material according to claim 6 in preparing a negative electrode for a sodium ion battery.

8. A sodium ion battery negative electrode, characterized in that: The negative electrode of the sodium ion battery is prepared by mixing a conductive agent, a binder, a solvent and the pine wood-based hard carbon material according to claim 6 to obtain a slurry, coating the obtained slurry on a current collector, and drying the slurry to obtain the negative electrode of the sodium ion battery.

9. The sodium ion battery negative electrode according to claim 8, characterized in that: The mass ratio of the conductive agent, the binder and the pine wood-based hard carbon material is (1-4): (1-8):

94.

10. A sodium ion battery, characterized in that: It comprises a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode is the negative electrode of the sodium ion battery according to claim 8.

Citation Information

Patent Citations

  • Pyrolysis hard carbon material with longitudinal pore structure and preparation method and application thereof

    CN108315028A

  • Preparation method of sodium ion battery hard carbon negative electrode material

    CN116395670A

  • Sodium ion battery and preparation method thereof

    CN118099357A

  • Lignocellulose phenolic resin / doped bamboo-based porous carbon derived hard carbon composite material, preparation method and application

    CN118239469A

  • Preparation method of hard carbon material for negative electrode of sodium ion battery and sodium ion battery

    CN118373408A

Cited By

  • Pine tree-based hard carbon negative electrode material and preparation method and application thereof

    CN122079151A